Verbascoside down‐regulates some pro‐inflammatory signal transduction pathways by increasing the activity of tyrosine phosphatase SHP‐1 in the U937 cell line. Issue 7 (21st March 2015) - Pesce, Mirko; Franceschelli, Sara; Ferrone, Alessio; De Lutiis, Maria Anna; Patruno, Antonia; Grilli, Alfredo; Felaco, Mario; Speranza, Lorenza
Abstract Polyphenols are the major components of many traditional herbal remedies, which exhibit several beneficial effects including anti‐inflammation and antioxidant properties. Src homology region 2 domain‐containing phosphatase‐1 (SHP‐1) is a redox sensitive protein tyrosine phosphatase that negatively influences downstream signalling molecules, such as mitogen‐activated protein kinases, thereby inhibiting inflammatory signalling induced by lipopolysaccharide (LPS). Because a role of transforming growth factor β‐activated kinase‐1 (TAK1) in the upstream regulation of JNK molecule has been well demonstrated, we conjectured that SHP‐1 could mediate the anti‐inflammatory effect of verbascoside through the regulation of TAK‐1/JNK/AP‐1 signalling in the U937 cell line. Our results demonstrate that verbascoside increased the phosphorylation of SHP‐1, by attenuating the activation of TAK‐1/JNK/AP‐1 signalling. This leads to a reduction in the expression and activity of both COX and NOS. Moreover, SHP‐1 depletion deletes verbascoside inhibitory effects on pro‐inflammatory molecules induced by LPS. Our data confirm that SHP‐1 plays a critical role in restoring the physiological mechanisms of inducible proteins such as COX2 and iNOS, and that the down‐regulation of TAK‐1/JNK/AP‐1 signalling by targeting SHP‐1 should be considered as a new therapeutic strategy for the treatment of inflammatory diseases.